Picture Research The Work of Intermediation from Pre-Photography to Post-Digitization - Vestberg, Nina Lager (Leonardo, 2023)
An intimate foray into the invisible work that made it possible for pictures to circulate in print and online from the 1830s to the 2010s.Picture Research focuses on how pictures were saved, stored, and searched for in a time before scanners, servers, and search engines, and describes the dramatic difference it made when images became scannable, searchable, and distributable via the internet. While the camera, the darkroom, and the printed page are well-known sites of photographic production that have been replaced by cell phones, imaging software, and websites, the cultural intermediaries of mass-circulation photography-picture librarians and researchers, editors, and archivists-are less familiar. In this book, Nina Lager Vestberg artfully details the range of research skills, reproduction machinery, and communication infrastructures that was needed to make pictures available to a public before digitization.Drawing on documents and representations across a range of cultural expressions, Picture Research reveals the intermediation that has been performed by skilled workers in a variety of roles, making use of pre-photographic, photographic, and digital machineries of capture, accumulation, extraction, and transmission. Tracing a history of the modern pictorial economy from the pre-photographic 1830s to the post-digitized 2010s, it makes visible and explicit the invisible labor that has built-and still sustains-the visual commodity culture of everyday life.